2020
DOI: 10.3138/cpp.2020-089
|View full text |Cite
|
Sign up to set email alerts
|

Public Responses to Policy Reversals: The Case of Mask Usage in Canada during COVID-19

Abstract: La maladie du coronavirus 2019 (COVID-19) a poussé les organismes de santé publique et autres respon sables gouvernementaux à apporter des changements rapides, importants et parfois contradictoires aux politiques, en réaction à la nouvelle information. Les auteurs étudient les répercussions de ces change ments sur l'adhésion du public à ces décisions en se penchant sur le cas de l'évolution des directives quant à l'usage du masque par les personnes asymptomatiques. Les recommandations officielles relatives à l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 4 publications
2
32
1
Order By: Relevance
“…Wearing face masks has the lowest rate of adherence as only approximately 67% of the adult population report wearing a mask. The proportion is similar to a recent Canadian study that found 63% of respondents reported wearing masks during in late May 2020 (Mohammed, Johnston, and van der Linden 2020), but well below the proportions in Singapore or the Philippines, where over 90% of adults wear a mask (CFR 2020). The low use of face masks is especially problematic given how critical it is for reducing transmission of the virus (Brankston et al 2020) and for lowering mortality rates (WHO 2020).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Wearing face masks has the lowest rate of adherence as only approximately 67% of the adult population report wearing a mask. The proportion is similar to a recent Canadian study that found 63% of respondents reported wearing masks during in late May 2020 (Mohammed, Johnston, and van der Linden 2020), but well below the proportions in Singapore or the Philippines, where over 90% of adults wear a mask (CFR 2020). The low use of face masks is especially problematic given how critical it is for reducing transmission of the virus (Brankston et al 2020) and for lowering mortality rates (WHO 2020).…”
Section: Resultssupporting
confidence: 85%
“…However, maskwearing in countries around the world ranges from 1% in Denmark and Finland to over 90% in Singapore and the Philippines, as adherence is greatly influenced by government regulations (CFR 2020). Canadian mask usage has gradually increased from 10% at the start of the pandemic in March 2020 to approximately 63% in late May (Mohammed, Johnston, and van der Linden 2020). The gradual change reflects shifts in the importance attributed to mask usage by public health officials.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]10], argue that face masks can reduce the spread of . Our paper also complements recent work on non-pharmaceutical interventions in various countries [ [14][15][16][17] and in Canada [18][19][20][21].…”
Section: /17supporting
confidence: 62%
“…Canadians viewed measures like mask-wearing as a means to protect others, not just themselves (van der Linden and Savoie 2020). Canadians also appeared to have formed these policy preferences based on the perceived seriousness of the pandemic and trust in the ability of government to lead appropriately (Sevi et al 2020;Mohammed, Johnston, and van der Linden, 2020). As a result, policymaking has been more cooperative in the Canadian experience.…”
Section: Discussionmentioning
confidence: 99%